Complications of Female Incontinence and Pelvic Reconstructive Surgery - Goldman, Howard B. (Springer International Publishing : Imprint: Humana Press, 2017)
The second edition of this text reviews the prevention, evaluation and management of complications arising from female pelvic surgery. As the field has advanced and now become its own recognized subspeciality offering Board Certification there is even more interest in this area. This edition provides more specific detail of potential complications of robotic female pelvic surgery, different categories of midurethral slings and specific transvaginal apical procedures. There are unique complications based on the specific mode of sling placement or apical repair and they are further subdivided in this text. Potential complications of both routine and specialized vaginal procedures such as transvaginal slings, cystocele and rectocele repairs, urethral diverticulectomy, and transvaginal mesh repairs are reviewed. The chapters are divided by procedure allowing the reader to easily find what they are looking for. Images and diagrams of methods of evaluation and repair of these complications are included. The second edition of Complications of Female Incontinence and Pelvic Reconstructive Surgery should serve as a reference allowing the surgeon quick and ready access to information about the complications of female pelvic surgery procedures - including detail on how to prevent, identify and manage them.
Keywords: Medicine.; Gynecology.; Nephrology.; Urology.; elektronické knihy; electronic books